The potential global distribution of an emerging forest pathogen, Lecanosticta acicola, under a changing climate - Ogris, Nikica; Drenkhan, Rein; Vahalík, Petr; Cech, Thomas; Mullett, Martin; Tubby, Katherine (Frontiers in Forests and Global Change, 2023)
Brown spot needle blight, caused by Lecanosticta acicola, is an emerging forest disease of Pinus species originating from North America and introduced to Europe and Asia. Severity and spread of the disease has increased in the last two decades in North America and Europe as a response to climate change. No modelling work on spread, severity, climatic suitability, or potential distribution has been done for this important emerging pathogen. The objectives were to (1) identify which bioclimatic and environmental variables are most influential in the distribution of L. acicola; (2) compare four modelling approaches to determine which modelling method best fits the data; (3) examine the realized distribution of the pathogen under climatic conditions in the reference period; (4) predict the potential future global distribution of the pathogen under various climate change scenarios. These objectives were achieved using a species distribution modelling. Four modelling approaches were tested and altogether, eight models were developed. An ensemble of the three best models was used to make predictions for the potential distribution of L. acicola. Performance of the model ensemble was very good, with high precision (0.87) and very high AUC (0.94). The potential distribution of L. acicola was computed for five global climate models (GCM) and three combined pathways of Shared Socioeconomic Pathway and Representative Concentration Pathway (SSP-RCP). The actual distribution of L. acicola in the reference period 1971–2000 covered 5.9% of Pinus spp. area globally. However, the model ensemble predicted potential distribution of L. acicola to cover an average of 58.2% of Pinus species global cover in the reference period. Different climate change scenarios showed a positive trend in possible range expansion of L. acicola for the period 1971–2100. The average model predictions towards the end of the century showed the potential distribution of L. acicola rising to 62.2% of Pinus spp. area. However, the 95% confidence interval encompassed 35.7–82.3% of global Pinus spp. area in the period 1971–2000 and 33.6–85.8% in the period 2071–2100.